NGO-School Partnerships & Citizenship Education - Mirzayee, Sophia (Université d'Ottawa / University of Ottawa, 2021)
This research study assesses the successes as well as the challenges associated with NGO interventions for citizenship education in schools. This study also examines the extent to which formal school curricula and NGO curricula are aligned. The methodology consists of a qualitative research design using document analysis and semi-structured interviews. First, I offer an analysis of the Canadian and World Studies curriculum in Ontario. In addition, curricula used in school interventions by five Canadian NGOs are examined and analyzed comparatively with the CWS curriculum. I also interview several NGO staff members who are involved in school interventions and curriculum experts with extensive knowledge of Ontario curricula. The results of this research shed light on the extent of curricular alignment and/or disconnection within NGO-school partnerships and the extent to which partnerships facilitate citizenship education in the classroom. The findings also illuminate key strategies for strengthening NGO-school partnerships. Lastly, this research contributes to a community of learning practice for Canadian NGOs that conduct citizenship education programming.
Keywords: global citizenship; citizenship education; NGO-school partnerships; NGOs; curriculum; human rights education; sustainable development education; NGO educational resources; Ontario curriculum; active citizenship; critical citizenship; Canadian and World Studies; NGO school interventions